Quick & easy low-sugar recipes : lose weight, boost energy, fight fatigue - Graimes, Nicola (Watkins Publishing, 2010)
Eating low-sugar foods doesn't have to mean being condemned to a dull diet. This book features one hundred easy-to-follow recipes that are divided into Breakfasts & Brunches, Lunches & Dinners. It also includes delicious family favourites such as fruit crumbles, sponge puddings, biscuits and cakes